2022
DOI: 10.1097/rct.0000000000001359
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing Intrathyroid Parathyroid Adenoma from Colloid Nodules and Papillary Thyroid Carcinomas Using Multiphasic Multidetector Computed Tomography

Abstract: ObjectiveThe aim of the study is to determine whether multiphase multidetector computed tomography (4D-MDCT) can differentiate between intrathyroid parathyroid adenomas (ITPAs), colloid nodules, and papillary thyroid carcinoma (PTC).MethodsWe studied 22 ITPAs, 22 colloid nodules, and 11 PTCs in 55 patients. Hounsfield unit (HU) values of the nodules were measured on 4D-MDCT in the precontrast, arterial, venous, and delayed phases. Raw HU values, phase with peak enhancement, and washout percentages between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…On the contrary, there has been a report of mistaking intrathyroid parathyroid adenoma for thyroid carcinoma. [ 17 , 18 ] Debna et al [ 19 ] reported that using multiphase multidetector CT, intrathyroid parathyroid adenomas show higher peak enhancement in the arterial phase and rapid washout compared to colloid nodules and papillary thyroid carcinomas. However, this technique is only feasible in institutes equipped with multiphase multidetector CT and may come with additional costs and radiation exposure.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, there has been a report of mistaking intrathyroid parathyroid adenoma for thyroid carcinoma. [ 17 , 18 ] Debna et al [ 19 ] reported that using multiphase multidetector CT, intrathyroid parathyroid adenomas show higher peak enhancement in the arterial phase and rapid washout compared to colloid nodules and papillary thyroid carcinomas. However, this technique is only feasible in institutes equipped with multiphase multidetector CT and may come with additional costs and radiation exposure.…”
Section: Discussionmentioning
confidence: 99%